Pengaruh Someone To Talk Terhadap Mahasiswa Sekolah Tinggi Agama Islam Barus Dalam Menghadapi Tantangan Boarding School - Muslim Pohan; Suci Ramadhani Situmeang (Journal of Information System and Education Development, 2026)
This article study aims to analyze the influence of the "Someone to talk" program on the abilities of students at the Barus Islamic College of Religion in facing the challenges of the boarding school system. Dormitory life at a religious college requires students to adapt academically, socially, spiritually, and emotionally. Many students experience psychological stress, communication difficulties, and decreased motivation to learn due to limited sharing space and social support. The "Someone to talk" program is presented as an interpersonal communication-based mentoring approach that provides a safe space for students to share experiences, complaints, and problem-solving strategies